Multicultural urban spaces and the right to the city: the Italian local policies on immigration - Colloca, Carlo (SocietàMutamentoPolitica, 2020)
The paper proposes a reflection on the issue of the ‘production of localities’, activities regarding the making up of an individual self. This aspect helps to determinate collective identities and memories shared by migrants and natives, as far as hybrid dynamics belonging to different cultures situated in the same urban milieu, are concerned. Central to the concept of multiculturalism is the notion of difference. All models of multicultural cities require categorization of difference at some level. In the Italian society different experiences of local multicultural welfare highlight how local policies on immigration can give effect to the recognition of cultural differences in a given territory, although they can not affect the legal issues as vital as access to citizenship or the right to vote. Local authorities play a significant role in promoting forms of social inclusion of migrants and generative welfare.